METHODS OF MEASURING EDUCATIONAL OUTCOMES - Zakhia Akhmedovna Narimbetova; Aidin Turdialieva (Modern American Journals, 2025)
This article analyzes the concept of measurement in the educational environment, its essence, key elements, and methods. It examines the differences between concrete and abstract characteristics of assessment objects, as well as the classification of measurement methods and scales used in educational practice.
Keywords: Measurement, elements of measurement, indirect measurement, direct measurement, analytical measurement, measurable property, measuring instrument, scale, measurement scale with symbols, measurement scale with numbers.